All the Ghosts in the Machine : The Digital Afterlife of Your Personal Data - Kasket, Elaine (2020)
Seen any ghosts on your smartphone lately? As we're compelled to capture, store and share more and more of our personal information, there's something we often forget. All that data doesn't just disappear when our physical bodies shuffle off this mortal coil. If the concept of remaining socially active after you're no longer breathing sounds crazy, you might want to get used to the idea. Digital afterlives are a natural consequence of the information age, a reality that barely anyone has prepared for - and that 'anyone' probably includes you. In 'All the Ghosts in the Machine', psychologist Elaine Kasket sounds a clarion call to everyone who's never thought about death in the digital age.
Keywords: Death -- Social aspects; Digital media -- Social aspects; Immortality; Personal information management; Family and Relationships